Divergent effects of successive drought and flooding on photosynthesis in wheat and barley - Saha, Shukanta; Johnson, Giles N. (Frontiers in Plant Science, 2025)
Climate change is leading to increases in extreme weather events, notably increasing both droughts and floods, which undermine food security. Although each stress individually has been well studied, little is known about the response of cereals to successive water stresses, condition that often occurs in real-world scenarios. To address this gap, we have compared physiological responses of wheat and barley cultivars to cycles of drought and flooding. We show that these species show different responses to each other and that successive stresses result in different responses to single stresses. Plants were subjected to control, drought or flooding treatments for 15 days. Following that, previously stressed plants were exposed to a further stress – drought followed by flooding (D-F) or flooding followed by drought (F-D) for a further 15 days. These cereals showed contrasting responses both to drought or flooding alone and to successive stresses (D-F or F-D). Barley retained photosynthetic capacity when exposed to single- drought or flooding, whereas wheat responded to both stresses with significant declines in CO2 assimilation capacity by 41% and 31% in response to drought or flooding, respectively -primarily due to stomatal closure. However, the first exposure to water stress impacts the inhibition of photosynthesis during subsequent stress. The effect of subsequent water stress – drought or flood –was continued and aggravated by the previous stress in wheat. Importantly, non-stomatal factors were induced, which reduced Photosystem II efficiency (62% and 49%) and chlorophyll content (35% and 47%) in wheat under D-F and F-D stress. By contrast, barley retained its photosynthetic capacity under D-F stress by acclimating, with 41% reduced shoot growth, while F-D treatment induced abnormal stomatal development. Both treatments resulted in the accumulation of carbon in tissues. Overall, we conclude that sensitivity to a stress is increased by the exposure to a previous stress, with F-D stress having the largest effect, while barley is relatively more tolerant than wheat highlighting it as the more robust cereal crop under fluctuating water conditions.